Agency costs and transaction costs as determinants of the dividend payment rate in Chile - Maquieira V., Carlos; Danús S., Mónica (Estudios de Administración, 1998)
We study the determinants of the dividend payout ratio considering a model that minimizes the sum of transaction and agency costs. Using a cross-sectional analysis on a sample of 60 Chilean public traded companies from 1986 to 1992, we examine the relationship between the dividend payout ratio and the expected growth rate, the beta, the percentage of shares helds by insiders and the number of stockholders. We find a positive and statistically significant relationship between the dividend payout ratio and the expected growth rate, which can be consistent with the signaling hypothesis.